Intentions to Use Mobile Food Delivery Application: A Theory of Planned Behavior and Technology Acceptance Model Approaches - Makhlouf, Asma (2024)
This study investigates the factors influencing Algerian customers' intention to use food delivery applications. Drawing on the theory of planned behavior and the technology acceptance model, the research employs a quantitative approach using a sample of 213 participants with prior experience in ordering food via food delivery applications. The findings indicate that attitude, subjective norms, and perceived usefulness positively and significantly influence food delivery applications usage intention, while perceived ease of use does not have a significant effect. This study is, to the best of the authors' knowledge, the first to explore these factors in the Algerian context. The study contributes to the literature by providing insights into consumer behavior in emerging markets and offers practical recommendations for food delivery service providers to enhance user engagement, improve service offerings, and drive adoption. These findings are particularly relevant for companies looking to navigate the evolving landscape of digital commerce in Algeria and similar emerging markets.